In Pursuit of Mobile Prey: Martu Hunting Strategies and Archaeofaunal Interpretation. Issue 1 (20th January 2009) - Bird, Douglas W.; Bird, Rebecca Bliege; Codding, Brian F.
Abstract : By integrating foraging models developed in behavioral ecology with measures of variability in faunal remains, zooarchaeological studies have made important contributions toward understanding prehistoric resource use and the dynamic interactions between humans and their prey. However, where archaeological studies are unable to quantify the costs and benefits associated with prey acquisition, they often rely on proxy measures such as prey body size, assuming it to be positively correlated with return rate. To examine this hypothesis, we analyze the results of 1, 347 adult foraging bouts and 649 focal follows of contemporary Martu foragers in Australia's Western Desert. The data show that prey mobility is highly correlated with prey body size and is inversely related to pursuit success—meaning that prey body size is often an inappropriate proxy measure of prey rank. This has broad implications for future studies that rely on taxonomic measures of prey abundance to examine prehistoric human ecology, including but not limited to economic intensification, socioeconomic complexity, resource sustainability, and overexploitation.